Hemorrhagic and ischemic outcomes of Heparin vs. Bivalirudin in carotid artery stenting: A meta‐analysis of studies. Issue 4 (16th August 2016) - Omran, Jad; Abdullah, Obai; Abu‐Fadel, Mazen; Gray, William A; Firwana, Belal; Drachman, Douglas E; Mahmud, Ehtisham; Aronow, Herebert D; White, Christopher J; Al‐Dadah, Ashraf S
Abstract : Introduction: Bivalirudin, has been shown to have comparable efficacy and better safety profile when compared to unfractionated heparin (UFH) in percutaneous coronary interventions. Bivalirudin's safety in carotid artery stenting (CAS) was associated with better outcomes than heparin in some studies. In this Meta analysis we examine the hemorrhagic and ischemic outcomes associated with Bivalirudin compared to UFH during CAS. Methods: A comprehensive literature search was conducted with the electronic databases MEDLINE, EMBASE, and CENTRAL. Random‐effects meta‐analysis method was used to pool risk ratio (RR) for both Heparin and Bivalirudin with 95% confidence interval (CI). Study outcomes included hemorrhagic complications; major/minor bleeding and intracranial hemorrhage (ICH) as well as ischemic complications including ischemic stroke, myocardial infarction, and 30 day mortality. Results: A total of four studies were included enrolling 7, 784 patients. Compared to UFH, Bivalirudin was associated with significantly lower major bleeding events with a relative risk (RR) of 0.53 (95% CI: 0.35–0.80; I 2  = 0%). Minor bleeding events were significantly lower in the Bivalirudin group with a RR of 0.41 (95% CI: 0.2–0.82; I 2  = 0%). Looking into other outcomes, there were no significant differences between anticoagulation strategies in terms of ischemic stroke (RR 0.8, with 95% CI: 0.60–1.06), intracranial hemorrhage (RR 0.73 with 95% CI: 0.27–1.98), myocardial infarction (RR 1.01 with 95% CI: 0.59–1.73) or 30 day mortality (RR 0.83 with 95% CI: 0.47–1.47). Conclusion: Compared to UFH, Bivalirudin is associated with lower bleeding risk when used during CAS. © 2016 Wiley Periodicals, Inc.